The COVID-19 pandemic reveals the wide-ranging role of biobanks - Juozapaitė, Dovilė; Minkauskas, Mantas; Laurinaitytė, Inga; Simutytė, Martyna; Griškevičius, Laimonas; Naumovas, Daniel (Frontiers in Public Health, 2023)
The pandemic of COVID-19 reached an unprecedented scale in terms of spread and deaths, its mitigation required a joint effort of governments, hospitals, private companies and other organizations. One type of organization that could undertake a major role in the process is biobank – a mediator between clinical practice and research. Naturally, biobanks are well equipped to alleviate the burden of a pandemic with their expertise in biospecimen and health information collection, sample preparation and storage, bioethics and project management. Here, we present the participation of Vilnius Santaros Klinikos Biobank (BB VSK), Lithuania in the overall management of the pandemics on the national level. We further discuss the role of biobanks in preparation and management of future pandemics.